Intraosseus access vs ecoguided peripherical venous access in emergency and urgency: a systematic review - Gerlando, Fiorenza; Scaccaglia, Davide; Artioli, Giovanna; Sarli, Leopoldo; Romano , Rita (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: Ensuring vascular access in emergency conditions is critical. Peripheral venous catheters (CVP) are the most used devices in clinical practice, even though their positioning can result difficult, causing delay in life-support treatments with possible critical results. Ultrasounds allow you to view blood vessel in real time, for this reason they could result helpful during use. Another option for the vascular access can be intraosseous access (I.O.), by introducing a needle directly in the bone marrow cavity. This review aim is to examine what typology of vascular access is best for the drug delivery in emergency/urgency in international and national literature. Methods: Bibliographical research was conducted by consulting the main biomedical databases through keywords and MESH terminology. In this review 21 articles published in the last 7 years have been included. They were published in English, Italian and French. Results: Contraindications and complications of I.O and of ultrasound-guided CVP positioning are limited. I.O access finding attempts are as fast as CVP positioning attempts but with a higher chance of success. Furthermore, ultrasound-guided CVP insertion is more comfortable for patients, it minimizes delays in medical treatment and it guarantees a better healthcare, with high percentage of right venous catheter placement. Conclusions: Intraosseous access is recommended for severely compromised patients; the ultrasound guide is a very useful tool when peripheral vascular areas are difficult to detect with only the palpation, it would be more appropriate in situations of urgency than that of emergency.